TEMPORALITAS HADIS; REINTERPRETASI HADIS-HADIS KLASIK DI TENGAH ARUS MODERNITAS - Moh. Misbakhul Khoir (IAIN Kediri, 2020)
The relation between the Hadith and the past situation is a reality that cannot be denied. The Prophet lived 62 years in the 6th Century AD. He did not live eternally, nor witnessed any changes in world civilization from time to time. So naturally, if what is contained from the Hadith, sometimes found typical features of classical Arabic civilization. This fact, if it is not taken into consideration in understanding the Hadith, surely the Hadith will be difficult to adapt at a different tempo from the time the Hadith was born. New efforts are needed to address this problem. Some efforts that emerged as a solution to the problem were the understanding of the Hadith by considering the setting of the socio-historical context when the Hadith was revealed, also by distinguishing means and goals, and by looking at Muhammad's role and function. So that people will get a clearer meaning and more focused on the core objectives of the Hadith (universal meaning), rather than just being trapped in the textuality of the Hadith which has a strong attachment to time (epoch). Thus, if this is applied, the Hadith is able to become a teaching of Islam that is sahih li kulli wa wa al-makan era and is able to provide total benefits.Keywords: Temporality, Classical Hadith, Modernity